Effects of Fermented Liquid Feed with Compound Probiotics on Growth Performance, Meat Quality, and Fecal Microbiota of Growing Pigs - Mengting Ji; Xiaoyin Rong; Yifan Wu; Haonan Li; Xiaolei Zhao; Yan Zhao; Xiaohong Guo; Guoqing Cao; Yang Yang; Bugao Li (Animals)
Feed fermentation enhances feed nutrition and animal health, but its impact on the gut microbiota of young pigs remains unclear. This study aimed to evaluate the effects of a probiotic fermented feed, which includes Lactobacillus plantarum, Pediococcus pentosaceus, Bacillus subtilis, and Bacillus coagulans, on the growth performance, meat quality, and intestinal microbiota of growing pigs. We randomly assigned 24 Duroc × Landrace × Landrace pigs to two groups: a control (Ctrl) group and the fermented liquid feed (FLF) group, with three replicate pens per group and four pigs per pen. Results indicated that the FLF group experienced a significant decrease in anti-nutritional factors like α-conglycinin and β-conglycinin. In addition, the average daily gain of pigs in the FLF group increased significantly, while the feed conversion ratio and shear force decreased. HE staining showed that the FLF group had notably enhanced villus height in the jejunum and ileum. 16S rRNA sequencing revealed a marked increase in the relative abundance of certain microbes in the FLF group, which were predominantly associated with carbohydrate and amino acid metabolism. These results indicated that compound probiotic FLF can elevate feed quality, enhance the growth performance of growing pigs, and ameliorate the structure of the gut microbiota.